Remapping the Chemical Space and the Pharmacological Space of Drugs: What Can We Expect from the Road Ahead? - Lucas Silva Franco; Bárbara da Silva Mascarenhas de Jesus; Pedro de Sena Murteira Pinheiro; Carlos Alberto Manssour Fraga (MDPI AG, 2024)
This work examines the current landscape of drug discovery and development, with a particular focus on the chemical and pharmacological spaces. It emphasizes the importance of understanding these spaces to anticipate future trends in drug discovery. The use of cheminformatics and data analysis enabled in silico exploration of these spaces, allowing a perspective of drugs, approved drugs after 2020, and clinical candidates, which were extracted from the newly released ChEMBL34 (March 2024). This perspective on chemical and pharmacological spaces enables the identification of trends and areas to be occupied, thereby creating opportunities for more effective and targeted drug discovery and development strategies in the future.